Effect of clonidine on carcass composition of growing pigs and approach to the mechanism of the effect - WANG Lei-jie; ZHAN Xiu-an; XU Zi-rong; ZHU Shun-da (浙江大学学报. 农业与生命科学版, 2005)
Sixty growing pigs (Daroc (Landrace (Yorkshine) were used to study the effect of clonidine on carcass composition and its mechanism. The results showed that supplementation of 0.5 mg/kg clonidine to feed increased lean meat percentage and eye muscle area of pigs by 5.29%(P<0.01) and 8.41%(P<0.01), weight of the longissimus dorsi, biceps femoris and quadriceps femoris by 13.77% (P<0.01), 11.11%(P<0.05) and 8.93%(P<0.05), and decreased fat percentage and back fat thickness by 9.53%(P<0.01) and 10.34%(P<0.05), respectively. In serum, GH and IGF-1 level were raised (P <0.05), urine nitrogen and triglyceride concentration decreased (P<0.05), and free fatty acids increased (P<0.05). In subcutaneous fat tissues, the malic dehydrogenase and glucose-6-phosphate dehydrogenase activities were lowered (P<0.01), and the hormone sensitive lipase activities improved (P<0.05).